Analisis Hubungan E-Commerce terhadap UMKM di Indonesia - Hafitasari, Itha Afifah; Adzani, Dara Ayu; Mafruhat, Ade Yunita (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
The purpose of this study was to determine the relationship between E-Commerce and Micro, Small and Medium Enterprises (MSMEs) in Indonesia. This is in line with the phenomenon of a significant increase in e-commerce in 2017 to 2021 which is considered to be able to encourage the development of MSMEs in Indonesia. This research uses quantitative research with simple linear regression analysis techniques and correlation analysis. The type of data used in this study uses time series data from 2011 to 2019 and data analysis is processed using Eviews 12 software. The results of the correlation analysis show a very strong relationship between ecommerce and MSMEs. In addition, the results of a simple linear regression analysis show that e-commerce transactions can affect the development of MSMEs in Indonesia. MSMEs are considered to have contributed to Indonesia's Gross Domestic Product (GDP), therefore it is important for a country to encourage the increase in MSMEs in order to increase economic growth in Indonesia as a whole and help restore the national economy.